FMR1 Key Biomarker in Fragile X Syndrome- A Comprehensive Review - Smitha Nayak; Ramdas Bhat (International Journal of Brain Sciences, 2024)
Fragile X Syndrome (FXS) is a complicated neurodevelopmental condition that causes intellectual disabilities, behavioural issues, and a variety of physical symptoms. Central to understanding FXS is the Fragile X Mental Retardation 1 (FMR1) gene, pivotal in the disorder's pathogenesis. This review examines FMR1 as a key biomarker in FXS, drawing on recent research insights. The FMR1 gene, situated on the X chromosome, encodes the fragile X mental retardation protein (FMRP), which is essential for synaptic function and brain development. Mutations in FMR1, including CGG repeat expansions, cause FXS, resulting in cognitive and behavioural impairments. Advances in molecular genetics elucidate FMR1 dysfunction and its roles in FXS phenotypes. DNA testing for FMR1 mutations is used in diagnostic techniques, which is critical for accurate diagnosis and genetic counselling. FMR1 serves as a biomarker for disease monitoring and treatment evaluation. Emerging therapies targeting FMR1-related pathways offer promise for FXS intervention, highlighting FMR1 as a therapeutic target. Understanding FMR1's roles in FXS pathophysiology informs precision medicine approaches. Elucidating FXS's molecular basis and leveraging FMR1 as a biomarker aim to advance diagnostics, refine therapies, and improve outcomes. This review underscores FMR1's pivotal role in FXS research and clinical practice, emphasizing its potential as a key biomarker for guiding precision medicine interventions.
Keywords: Biomarker; FMR1 (Fragile X Mental Retardation 1) gene; Fragile X syndrome; Neurodevelopmental disorder; Precision medicine